POLITIK LUAR NEGERI INDONESIA TERHADAP MALAYSIA DALAM MEMPERTAHANKAN KEPEMILIKAN TERHADAP BLOK AMBALAT PASCA KONFLIK PULAU SIPADAN DAN LIGITAN TAHUN 2012-2105 - Ibnu Pramana Putra; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the foreign politics of Indonesia toward Malaysia in conflict of bloc Ambalat after Sipadan and Ligitan Conflict in 2012-2015. Ambalats are sea territory between Indonesia and Malaysia in Kalimantan teritory. Ambalat have potencial in natural resources likes oil and gas. In 2005 Malaysia give a exploration right for Shell Company and its make increase of conflict with Indonesia cause based on UNCLOS 1982 Ambalat sea are Indonesia territory with the Archipelago State status.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the foreign politics of Indonesia toward Malaysia in conflict of bloc Ambalat after Sipadan and Ligitan Conflict. The theories applied in this research are realism perspective with decision making theory by Richard Snyder.The conclusion of this research that foreign politics of Indonesia toward Malaysia in conflict of bloc Ambalat after Sipadan and Ligitan Conflict are diplomacy ways. The foreign politics are Indonesia government held a daily patroll in Ambalat sea to anticipation of claim and criminall act, Indonesia government sent a diplomatic note to Malaysia as protess about Malaysia claims, Indonesia built a military based in Ambalat sea (Karang Unarang) and Indonesia government gives a exploration rights for ENI E&P Company.Key words: foregin, politics, conflice and sea territory